1973
DOI: 10.1073/pnas.70.9.2702
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Extracts and Steroid Hormones in the Control of 3T3 Cell Growth

Abstract: Results are reported showing that pituitary extracts stimulate growth of 3T3 cells, an established line of mouse fibroblast. Cells were cultured in medium containing an organic buffer (HEPES; N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid), which increases the serum requirement for cell growth. The pituitary growth-promoting activity is (a) not dialyzable; (b) thermolabile; (c) protease sensitive; and (d) enhanced by hydrocortisone (a steroid hormone). Activity was quantitatively assayed by measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0
20

Year Published

1975
1975
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 336 publications
(121 citation statements)
references
References 14 publications
1
100
0
20
Order By: Relevance
“…The concentration of EGF required for half-maximal induction of the activator substance (Fig. 3) is very similar to that required for half-maximal mitogenic response in 3T3 and other animal cells (12,(18)(19)(20) (14). We are therefore interested in developing an improved preparative procedure that will yield a 3T3 nuclear preparation more susceptible to the stimulatory effects of EGF-treated cell extract.…”
mentioning
confidence: 89%
“…The concentration of EGF required for half-maximal induction of the activator substance (Fig. 3) is very similar to that required for half-maximal mitogenic response in 3T3 and other animal cells (12,(18)(19)(20) (14). We are therefore interested in developing an improved preparative procedure that will yield a 3T3 nuclear preparation more susceptible to the stimulatory effects of EGF-treated cell extract.…”
mentioning
confidence: 89%
“…Glucocorticoids stimulate the growth of "normal" 3T3 cells (1,12), a somewhat intriguing fact because normal fibroblasts are inhibited by glucocorticoids (13,14). Therefore it is not surprising that ST1 cells are inhibited by glucocorticoids although the inhibitory activity could not be perfectly correlated with glucocorticoid activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, purified LH obtained from another source was ineffective on the ovarian cells. At the same time a post-doctoral fellow in the lab found that NIH-LH was growth stimulatory for 3T3 cells, which suggested a more general activity of a contaminating substance (Armelin 1973). Pursuing this observation, the contaminating activity in NIH-LH was shown to be the novel pituitary-derived growth factor basic FGF (Gospodarowicz et al 1974).…”
Section: Introductionmentioning
confidence: 92%